The Republic of Turkey and its Unresolved Issues
XVIII, 369 p. 21 illus., 20 illus. in color.
Keywords: Written by some of Turkey's best young scholars, this book's engaging research and critical analyses provide fresh insights into the country's recurring problems, from violations of minority and women's rights to attacks on the environment and education, the role of the military and emergency rule, and relations with Russia. The authors parse history for the structures and mechanisms that cause these issues to recur, but also to understand what has changed and why. The book is a rich, easily accessible and eye-opening rethinking of Turkish history that belongs on the desk of anyone interested in understanding today's Turkey and its future. ---Jenny White, Professor Emerita, Stockholm University Institute for Turkish Studies Why a century after its foundation, the Republic of Turkey remain a land of massive state coercion and violence, never ending political unrest and impressive economic depressions, denial of past mass-crimes, and praxis of internal and external war, widespread corruption and paramilitarisations? This extremely well-informed and theoretically robust volume sheds a new light on this country’s past and present crisis, but also presents fresh perspectives to imagine a radically distinct future. ----Hamit Bozarslan, Professor and Director of Studies at the École des Hautes Études en Sciences Sociales This open access book explores the Republic of Turkey’s unresolved issues that have persisted over the past 101 years. It adopts an interdisciplinary perspective to explore the challenges facing the country to critically analyse the broader historical, political, economic, social and psychological dimensions that intersect with these challenges. It offers a rich and nuanced understanding of Turkey’s complex history and contemporary issues, covering topics that have often been undermined or silenced, including but not limited to the Armenian and Dersim genocides, xeno-racism, feminist approaches to sexual morality, queer resistances, environmental movements, and the right to the city. Pınar Dinç is an associate professor of political science at the Department of Political Science and the Centre for Advanced Middle Eastern Studies, Lund University. Olga Selin Hünler is an associate professor of psychology at Acıbadem University.